Evaluation of the Use of Web-Based Library Management System at I Gusti Bagus Sugriwa State Hindu University Denpasar - Muliani, Ni Made; Kartika, Luh Gede Surya; Wijaya, I Komang Wisnu Budi; Giri, I Putu Agus Aryatnaya; Wiguna, I Gusti Ngurah Dwi Candra (Information Technology and Science (ITScience), 2025)
Libraries as the heart of higher education play a vital role in supporting the Tri Dharma, particularly in academic and research development. The advancement of information technology demands innovation in library services, one of which is the adoption of Web-Based Library Management Systems (WLMS). This study, entitled Evaluation of the Use of Web-Based Library Management System at I Gusti Bagus Sugriwa State Hindu University, Denpasar, aims to evaluate the effectiveness, challenges, and strategic significance of WLMS implementation using the Technology Acceptance Model (TAM) and the Technology–Organization–Environment (TOE) framework. A sequential explanatory design was applied, combining quantitative surveys and qualitative interviews with 39 respondents consisting of librarians, lecturers, and students. Quantitative findings indicate very good results in perceived usefulness (PU), attitude toward use (ATU), behavioral intention (BI), and actual use (AU), while perceived ease of use (PEOU) scored in the “good” category. TOE-based analysis reveals supporting factors such as infrastructure availability, leadership commitment, and system accessibility, while inhibiting factors include unstable internet, data security concerns, insufficient training, and low digital literacy among users. These results demonstrate that although WLMS significantly improves accessibility, efficiency, and digital literacy, its sustainability requires continuous system optimization, technical support, and human resource development. This research concludes that WLMS adoption at I Gusti Bagus Sugriwa State Hindu University is largely successful but still needs strategic interventions to ensure long-term effectiveness and integration with the university’s mission of advancing Hindu knowledge and culture in the digital era.